Bordering two unions: Northern Ireland and Brexit - Sylvia de Mars; Colin Murray; Aiofe O'Donoghue; Ben Warwick (Policy Press, 2018)
How does Brexit change Northern Ireland's system of government? Could it unravel crucial parts of Northern Ireland's peace process? What are the wider implications of the arrangements for the Irish and UK constitutions? Northern Ireland presents some of the most difficult Brexit dilemmas. Negotiations between the UK and the EU have set out how issues like citizenship, trade, the border, human rights and constitutional questions may be resolved. But the long-term impact of Brexit isn't clear. This thorough analysis draws upon EU, UK, Irish and international law, setting the scene for a post-Brexit Northern Ireland by showing what the future might hold.
Keywords: 320; Brexit; European Union Law; Human rights law; Northern Ireland; Trade Law